Zinc and provitamin A biofortified maize genotypes exhibited potent to reduce hidden-hunger in Nepal - Dhakal, Krishna; Magar, Amar Bahadur Pun; Pokhrel, Keshab Raj; Baral, Bandhu Raj; Issa, Abdurahman Beshir; Shrestha, Hari Kumar; Vista, Shree Prasad (MDPI, 2022)
Zinc deficiency affects one third of the population worldwide, and vitamin A deficiency is a prevalent public health issue in Sub-Saharan Africa and South-Asia, including Nepal. Crop biofortification is the sustainable solution to these health—related problems, thus we conducted two different field trials in an alpha lattice design to identify zinc and provitamin A biofortified maize genotypes consistent and competitive in performance over the contrasting seasons (Season 1: 18 February to 6 July 2020 and Season 2: 31 August to 1 February, 2020/21). In our study, the performance of introduced maize genotypes (zinc—15 and provitamin A biofortified—24) were compared with that of the local check, focusing on the overall agro-morphology, yield attributes, yield, and kernel zinc and total carotenoid content. Zinc and total carotenoid in the tested genotypes were found in the range between 14.2 and 24.8 mg kg−1 and between 1.8 and 3.6 mg 100 g−1. Genotypes A1831-8 from zinc and EEPVAH-46 from provitamin A biofortified maize trial recorded kernel zinc and total carotenoid as high as 52.3, and 79.5%, respectively, compared to the local check (DMH849). The provitamin A genotypes EEPVAH-46 and EEPVAH-51 (total carotenoid: 3.6 and 3.3 mg 100 g−1), and zinc biofortified genotypes A1847-10 and A1803-42 (20.4 and 22.4 mg kg−1 zinc) were identified as superior genotypes based on their yield consistency over the environments and higher provitamin A and zinc content compared to the check. In addition, farmers can explore August sowing to harvest green cobs during December-January to boost up the emerging green cob business.